Extracting bioactive compounds for food products : theory and applications - Meireles, M. Angela A. (Contemporary food engineering, 2009)
The demand for functional foods and neutraceuticals is on the rise, leaving product development companies racing to improve bioactive compound extraction methods. This title details the engineering aspects of the processes used to extract bioactive compounds from their food sources.